2011
DOI: 10.5653/cerm.2011.38.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Functions of PIWI proteins in spermatogenesis

Abstract: Recently, a significant understanding of the molecular mechanisms regulating spermatogenesis has been achieved utilizing small RNA molecules (small RNAs), including small interfering RNAs (siRNAs), microRNAs (miRNAs), and Piwi-interacting RNAs (piRNAs) which emerged as important regulators of gene expression at the post-transcriptional or translation level. piRNAs are only present in pachytene spermatocytes and round spermatids, whereas miRNAs are expressed abundantly in male germ cells throughout spermatogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 52 publications
3
35
0
1
Order By: Relevance
“…PIWIL1 and PIWIL2 are members of the mouse Piwi family proteins (MIWI, MILI, and MIWI2) that play important roles in spermatogenesis through transcriptional and post-transcriptional regulation. Acting as a functional partner of Piwi family proteins, TDRD group of Tudor proteins were reported to be physiological binding partners of Piwi family proteins and coordinately work together in the regulation of spermiogenesis [54], [57]. Here in our findings, the fact that both PIWIs and TDRDs were identified among the male-biased genes is intriguing, suggesting that they may similarly work side by side in coordination of spermatogenesis.…”
Section: Discussionsupporting
confidence: 47%
“…PIWIL1 and PIWIL2 are members of the mouse Piwi family proteins (MIWI, MILI, and MIWI2) that play important roles in spermatogenesis through transcriptional and post-transcriptional regulation. Acting as a functional partner of Piwi family proteins, TDRD group of Tudor proteins were reported to be physiological binding partners of Piwi family proteins and coordinately work together in the regulation of spermiogenesis [54], [57]. Here in our findings, the fact that both PIWIs and TDRDs were identified among the male-biased genes is intriguing, suggesting that they may similarly work side by side in coordination of spermatogenesis.…”
Section: Discussionsupporting
confidence: 47%
“…Their contribution has been shown to be significant for processes ranging from protection of genome against transposon activity during spermatogenesis [11], [12] and stem cell maintenance [13], [14] to somatic regulation and establishment of epigenetic states [15][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that miRNAs, endogenous siRNAs (endo-siRNAs), and piRNAs are all expressed in the male germ cells and are required for spermatogenesis in animals [93,94]. miRNAs and endo-siRNAs are abundantly expressed in male germ cells throughout spermatogenesis, whereas piRNAs are only present in spermatocytes at the pachytene stage and in round spermatids [92,94]. The absolute requirement for miRNAs and endo-siRNAs for spermatogenesis has been shown by two initial studies where Dicer1 gene was knocked out in two different mouse models [95,96].…”
Section: Role Of Protamination In Male Infertilitymentioning
confidence: 99%
“…In comparison to miRNAs and siRNAs, piRNAs are longer (approximately 26-31 nucleotides in length), and their biogenesis, although not well understood, is independent of Dicer [91]. piRNAs and PIWI proteins are known to be essential for germ cell development and silencing of repetitive elements such as transposons [92].…”
Section: Role Of Protamination In Male Infertilitymentioning
confidence: 99%